Reliability of a method for evaluating porosity in denture base resins - Pero, Ana Carolina [UNESP] [UNESP]; Marra, Julie [UNESP]; Paleari, Andre Gustavo [UNESP]; de Souza, Raphael Freitas; Ruvolo-Filho, Adhemar; Compagnoni, Marco Antonio [UNESP] (Wiley-Blackwell, 2011)
Background:The method of porosity analysis by water absorption has been carried out by the storage of the specimens in pure water, but it does not exclude the potential plasticising effect of the water generating unreal values of porosity.Objective:The present study evaluated the reliability of this method of porosity analysis in polymethylmethacrylate denture base resins by the determination of the most satisfactory solution for storage (S), where the plasticising effect was excluded.Materials and methods:Two specimen shapes (rectangular and maxillary denture base) and two denture base resins, water bath-polymerised (Classico) and microwave-polymerised (Acron MC) were used. Saturated anhydrous calcium chloride solutions (25%, 50%, 75%) and distilled water were used for specimen storage. Sorption isotherms were used to determine S. Porosity factor (PF) and diffusion coefficient (D) were calculated within S and for the groups stored in distilled water. anova and Tukey tests were performed to identify significant differences in PF results and Kruskal-Wallis test and Dunn multiple comparison post hoc test, for D results (alpha = 0.05).Results:For Acron MC denture base shape, FP results were 0.24% (S 50%) and 1.37% (distilled water); for rectangular shape FP was 0.35% (S 75%) and 0.19% (distilled water). For Classico denture base shape, FP results were 0.54% (S 75%) and 1.21% (distilled water); for rectangular shape FP was 0.7% (S 50%) and 1.32% (distilled water). FP results were similar in S and distilled water only for Acron MC rectangular shape (p > 0.05). D results in distilled water were statistically higher than S for all groups.Conclusions:The results of the study suggest that an adequate solution for storing specimens must be used to measure porosity by water absorption, based on excluding the plasticising effect.
Keywords: acrylic resins; complete denture; physical properties; polymers; porosity